Strengthening Consumer Protection in Digital Transactions: A Legal Perspective on Click-Wrap Agreements Under the Consumer Protection Law - Hulman Panjaitan; Junimart Girsang; Moermahadi Soerja Djanegara; Md Hasnath Kabir Fahim (Jurnal Hukum, 2025)
This study examines the effectiveness of consumer protection in Indonesia’s digital transactions, with a focus on click-wrap agreements. It addresses three key questions: the normative application of consumer protection laws, the practical challenges in enforcing these laws in online markets, and strategies to strengthen legal safeguards. Using a normative and conceptual juridical approach, the research analyzes relevant legislation, including the consumer protection law, electronic information and transactions law, personal data protection law, Government Regulation Number 80/2019, and Minister of Trade Regulation Number 31/2023. Literature review and legal documents, such as academic studies, court decisions, and government policies, were also examined to assess compliance, identify ambiguous clauses, and evaluate protection mechanisms. Findings indicate that while Indonesia has legal framework guaranteeing consumer rights to accurate information, safety, compensation, and data privacy, practical enforcement remains limited. Click-wrap agreements often contain complex or non-negotiable clauses that reduce consumers’ ability to exercise their rights. Strengthening legal mechanisms, including online dispute resolution, enhanced capacity of the consumer dispute resolution agency, digital consumer literacy, and regulatory harmonization, is essential to bridge the gap between law and practice. Coordinated implementation of these measures can ensure effective, transparent, and equitable protection for digital consumers.